Fabrication of multiwalled carbon nanotube-surfactant modified sensor for the direct determination of toxic drug 4-aminoantipyrine - Jayant I. Gowda; Arunkumar T. Buddanavar; Sharanappa T. Nandibewoor (Elsevier, 2015)
A multi-walled carbon nanotube (MWCNT)-cetyltrimethylammonium bromide (CTAB) surfactant composite modified glassy carbon electrode (GCE) was developed as a novel system for the determination of 4-aminoantipyrine(AAP). The oxidation process was irreversible over the pH range studied and exhibited a diffusion controlled behavior. All experimental parameters were optimized. The combination of MWCNT-CTAB endows the biosensor with large surface area, good biological compatibility, electricity and stability, high selectivity and sensitivity. MWCNT-CTAB/GCE electrode gave a linear response for AAP from 5.0Ã10â9 to 4.0Ã10â8Â M with a detection limit of 1.63Ã10â10Â M. The modified electrode showed good selectivity against interfering species and also exhibited good reproducibility. The present electrochemical sensor based on the MWCNT-CTAB/GCE electrode was applied to the determination of AAP in real samples. Keywords: Voltammetry, Modified electrode, Diffusion controlled, 4-aminoantipyrine, Pharmacokinetic study